LA LEY DE MEMORIA HISTÓRICA Y LA BÚSQUEDA DE LOS DESAPARECIDOS EN ESPAÑA: UNA APROXIMACIÓN DESDE LA ARQUEOLOGÍA FORENSE - Bolaños, Aldo (2010)
The Law of Historical Memory in Spain (Law 52/2007 of 26 December) is intended to pave the way for thousands of victims of the Spanish civil war and Franco’s dictatorship (1939-1975) to be morally and economically repaired and also enable the search and return to their relatives in the remains of those forcibly disappeared or were executed extra-judicially. However, there is great debate about whether the Act, as currently posed, can help. The article discusses how the scientific procedures of forensic archeology are addressed by the Act, in some cases limiting it, and how to fix the Spanish state’s responsibilities to reach solutions for the problems of families and thousands from graves still left without dignity in Spanish territory. The essay reflects, indirectly, from the analysis of the Spanish Law of Historical Memory, about the problems of the approximately 15,000 missing persons who left the Peruvian internal conflict in which we have not yet developed a political process, legal–legal, humanitarian and scientific according to the claim of the relatives to recover their loved ones and the Peru´s need to dignify their landscapes, ie landscapes without mass graves.